ANALISIS PENGARUH DEBT TO EQUITY RATIO (DER), RETURN ON ASSET (ROA), UKURAN PERUSAHAAN, INFLASI DAN NILAI TUKAR TERHADAP RETURN SAHAM (Studi Kasus Pada Perusahaan Lembaga Keuangan Bank Dan Lembaga Non Bank yang Listed di Bursa Efek Indonesia Periode 2004 - 2007) - Simanjuntak, John Edward H. (JURNAL BISNIS STRATEGI, 2009)
Capital market considered to be one of investment medium which is good to get dividend, capital gain, and also other advantage. Especial condition which wanted by all investor to channel its fund through capital market is investment safeness. This safeness is obtained because all investor get clear information, timely and tail; as base in its investment decision making. The objectives of this research is to analyze the influence of Debt to Equity; Ratio (DER), Return On Asset (ROA), size, inflation and exchange rate toward stock return on bank financial institution and non bank financial institution. This research also used Chow Test to analyze the difference influence Debt to Equity Ratio Â· (DER), Return On Asset (ROA), size, inflation and exchange rate toward stock return on bank financial institution and non bank financial institution.The population in this research is bank financial institution and non bank financial institution that listed in Indonesian Stock Exchange since 2004 until 200 7 is counted 83 companies. Sampling technique in this research is purposive sampling. Sample of this research consists of 18 hank financial institution companies and 23 non bank financial institution companies. Analyze technique that use in this research is multiple linear regression and chow test.The result of this research shows that that adjusted R2 on bank financial institution is 20,6%, non bank financial institution is 16,6% and for all adjusted R2 is 23,8%. F test shows that in simultant on bank financial, non bank financial institution and all variable independent influence variable dependent. Chow Test result shows no difference influence of Debt to Equity Ratio (DER), Return On Asset (ROA), size, inflation and exchange rate toward stock return on bank financial and non bank financial institution. Investor can use the result of this research as a consideration before invest.